2006
DOI: 10.1097/01.jnen.0000218442.07664.04
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Protein Kinase C in Neurodegenerative Disease I

Abstract: Protein kinase Mzeta (PKMzeta), an atypical protein kinase C (PKC) isoform, plays a key role in the maintenance of long-term potentiation (LTP), a persistent enhancement of AMPA receptor-mediated synaptic transmission, as well as in the persistence of memory in Drosophila. Because memory impairment in Alzheimer disease (AD) has been attributed to disruption of synaptic plasticity, we investigated the expression and distribution of PKMzeta in this disorder. We found that PKMzeta accumulated in neurofibrillary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Previous results have shown that PKMζ is present in neocortex, including motor cortex [16][18]. We found that bilateral injections of the PKMζ inhibitor ZIP into the sensorimotor cortex of rats erased the sensorimotor memories learned in a skilled reach-to-grasp task [19].…”
Section: Discussionmentioning
confidence: 55%
“…Previous results have shown that PKMζ is present in neocortex, including motor cortex [16][18]. We found that bilateral injections of the PKMζ inhibitor ZIP into the sensorimotor cortex of rats erased the sensorimotor memories learned in a skilled reach-to-grasp task [19].…”
Section: Discussionmentioning
confidence: 55%
“…KIBRA also interacts with the protein kinase Mζ (PKMζ) (Buther et al, 2004), an active atypical PKC isoform that plays a role in LTP maintenance (Serrano et al, 2005) and memory (Drier et al, 2002). PKMζ accumulates in NFTs in human AD brain (Crary et al, 2006), raising the possibility of a mechanistic link between tau, KIBRA and PKMζ. Taken together, our results demonstrate that acetylated tau in AD disrupts one or more KIBRA-mediated signaling pathways that are crucial for the expression of synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…The assay’s procedures were based on those used in our previous studies (Lu et al, 2003, 2005; Li et al, 2008) and previous studies of Sacktor and colleagues (Sacktor et al, 1993; Hrabetova and Sacktor, 1996; Naik et al, 2000; Crary et al, 2006; Kelly et al, 2007; Yao et al, 2008). Loading buffer (4×; 16% glycerol, 20% mercaptoethanol, 2% SDS, 0.05% bromophenol blue) was added to each sample (3:1, sample:loading buffer) before boiling for 3 min.…”
Section: Methodsmentioning
confidence: 99%